Inside Cover Image, Volume 6, Issue 2. (March 2016) - Raies, Arwa B.; Bajic, Vladimir B.
Abstract : The inside cover image, by Vladimir B. Bajic and Arwa B. Raies, is based on the Advanced Review In silico toxicology: computational methods for prediction of chemical toxicity, DOI:10.1002/wcms.1240 . Abstract : The inside cover image, by Vladimir B. Bajic and Arwa B. Raies, is based on the Advanced Review In silico toxicology: computational methods for prediction of chemical toxicity, DOI:10.1002/wcms.1240 .